Observations on the use of the Becton Dickinson Fibrometer. Issue 3 (May 1965) - Wylie, C. R. R.; Fraser, C.
Abstract : An electro-mechanical instrument for use in both Thrombotest and Quick one-stage systems of anticoagulant control is described and the results obtained using it are compared with those obtained in the standard manual method. These figures show a very satisfactory degree of correlation, and it is concluded that the instrument would be of value in laboratories, particularly those controlling anticoagulant therapy by the Owren Thrombotest system.